Correction: Finding a safe space for learning and exploration: A qualitative study of recently diagnosed men's experiences of peer support for HIV in Sweden. - PLOS One Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0283570.].